NUMERICAL SIMULATION ON REAR SPOILER ANGLE OF MINI MPV CAR FOR CONDUCTING STABILITY AND SAFETY - Alief Avicenna Luthfie; Dedik Romahadi; Hanif Ghufron; Solli Dwi Murtyas (Universitas Mercu Buana, 2020)
Spoiler attached on the rear part of a car can generate drag force and negative lift force, called downforce. This drag force can increase air resistance to the car, meanwhile, a negative lift force can improve the car’s stability and safety. Refer to many researchers, the shape and the angle of the spoiler give different aerodynamic effects and therefore give a different value of drag force and lift force. Based on these facts, this study was focused on the analysis of different spoiler angle attached to a mini MPV car to drag and lift force generated by the spoiler. The method used in this study is a numerical simulation using the Computational Fluid Dynamics (CFD) technique. The analysis was carried out at different spoiler angle and car’s speed. The spoiler angles are -20o, -10o, 0o, 10o, and 20o. The car’s speeds are 40 km/h, 60 km/h, 80 km/h, 100 km/h, and 120 km/h. Then the drag and lift force and their coefficient generated by different spoiler angles were being investigated at specified speeds. The result shows that higher spoiler angles generate higher drag and lower lift. Spoiler angles higher than 0o generate negative lift force, otherwise generate positive lift force. Therefore, to increase a car’s stability and safety, it is recommended to use a spoiler angle higher than 0o. Based on the result, it is best to use spoiler angle 10o because it generates negative lift force with -0.05 lift coefficient and 0,68 drag coefficient.